If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -7x = 29 + -14x Solving 10 + -7x = 29 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 10 + -7x + 14x = 29 + -14x + 14x Combine like terms: -7x + 14x = 7x 10 + 7x = 29 + -14x + 14x Combine like terms: -14x + 14x = 0 10 + 7x = 29 + 0 10 + 7x = 29 Add '-10' to each side of the equation. 10 + -10 + 7x = 29 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = 29 + -10 7x = 29 + -10 Combine like terms: 29 + -10 = 19 7x = 19 Divide each side by '7'. x = 2.714285714 Simplifying x = 2.714285714
| 4(3x-3)=44 | | 3w^2-0.75w=0.5 | | 0.10x+0.5(6-x)=.10(6) | | 3(3y+1)=7(51-5y) | | 3(3y+1)=7(51+-5y) | | x+4y=3v | | 3(3y+1)=7(51-35y) | | 10+7x=29+14x | | 3(x+4)=5x-10 | | 8y^2=-9y+4 | | 10x-7=29-14x | | 81t^2+144t+64= | | 10-7x=29-14xr | | 3y-1+y+47=7y+50-5y | | 7x-11=2x+14 | | 17x+19y=-23 | | 19x+17y=-23 | | -17-10=7x+17 | | 7x-22=41 | | 5*12+10=4*12+p | | 5*-12+10=4*-12+p | | 5-12+10=4*-12+p | | 83=32x+10 | | 18-12+2+1= | | 60-4x=32x+16 | | 8x+4=6x+10 | | -19.48+x=28.03 | | 3x+8=-8-7x | | 10-3h=25 | | y=-4x+0 | | 5t+1=11 | | 82-5x=22x+16 |